MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN METODE TEAM GAME TURNAMENT PADA SISWA KELAS VII.1 SMP NEGERI 3 BATANGHARI TAHUN PELAJARAN 2012/2013 - Rustinah Rustinah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
The aim of this research is to improvestudent’s mathematics achievment in aljabar by using TGT method. The research was conducted on SMP N 3 Batanghari. This action research was executed in two cycles, each consisted of one action which was applied in 3-4 meeting with 2 x 35 minutes long duration.The analyzed resultof cycle 1 and 2 data observation was: the activity was clearly improved at second cycle by students actively answeres the problem that proposed by the teacher. By the observation data, it clearly showes that implementation of TGT on aljabar competence gave enough significant contribution toward students learning achievment. The result of average data observation was 65,43 with 13 unsuccessful students, with standard classical 66,67%. On the second cycle, the average score was 69,43 while the number of students who success 70% with 9 students who field. Although the result was not significant, it’s enough to prove that there is student’s learning achievement. The 3,33% improvement still make the researcher smile because the aljabar material is more difficult than other. Beside that problem, the average score of the class which reached 69,35 was difficult to be fulfilled, but by using TGT method, the score can be reached.Keywords: TGT Method, Aljabar, dan Achievment